Autophagy, apoptosis, and mitochondria: molecular integration and physiological relevance in skeletal muscle - Bloemberg, Darin (Am J Physiol Cell Physiol, 2019)
Apoptosis and autophagy are processes resulting from the integration of cellular stress and death signals. Their individual importance is highlighted by the lethality of various mouse models missing apoptosis or autophagy-related genes. In addition to their independent roles, significant overlap exists with respect to the signals that stimulate these processes as well as their effector consequences. While these cellular systems exemplify the programming redundancies that underlie many fundamental biological mechanisms, their intertwined relationship means that dysfunction can promote pathology. Although both autophagic and apoptotic signaling are active in skeletal muscle during various diseases and atrophy, their specific roles here are somewhat unique. Given our growing understanding of how specific changes at the cellular level impact whole-organism physiology, there is an equally growing interest in pharmacological manipulation of apoptosis and/or autophagy for altering human physiology and health.